Malay,world language a short history - Collins, James T. (Dewan Bahasa dan Pustaka, 2018)
The world's 290 million speakers of Malay draw their strength from the 1300-year history of Malay as a written language and the ever older oral traditions of their maritime ancestors. The Malay language has spread throughout Southeast Asia with outlier communities of Malay speakers in Holland, Australia and Sri Lanka.